P1-S2.01 Prevalence of HIV and sexually transmitted infections among clients of female sex workers in Karnataka, South India. (10th July 2011) - Shaw, S; Deering, K; Reza-Paul, S; Isac, S; Ramesh, B; Washington, R; Moses, S; Blanchard, J
Abstract : Introduction: Several studies have demonstrated the importance of commercial sex work in the transmission of HIV and other sexually transmitted infections (STIs) in India. Clients of female sex workers (FSWs) are thought to be an important bridging population for HIV and STIs. However, there is little information on basic characteristics of sex work clients. This study sought to describe the prevalence of HIV and other STIs, as well as examine the determinants of these pathogens, among a sample of clients in south India. Methods: Data were from a cross-sectional biological and behavioural survey of FSW clients from six districts in Karnataka State, India. The prevalence of HIV, syphilis, herpes simplex virus type 2 (HSV-2), chlamydia (CT) and gonorrhoea (GC) among clients was examined. Multivariable logistic regression models were used to analyse the socio-demographic, sexual behaviour and sex-work related characteristics related to the prevalence of each pathogen. Sampling weights and appropriate survey methods were utilised in regression models to account for a complex sampling design. Results: The total sample size was 2745. The average age of clients was 30.4 years (SE—0.3). Across the total sample, the prevalences of HIV, HSV-2, syphilis and CT/GC were 5.6%, 28.4%, 3.6% and 2.2%, respectively. The prevalence of HIV/STIs varied substantially across districts, reaching statistical significance for HIV (p<0.0001) and CT/GC (p=0.005). In multivariable models, duration of paying for commercial sex was associated with increased risk for HIV and HSV-2 (both AORs—1.1; 95% CI 1.0 to 1.1, p<0.0001). Clients using brothels as a main FSW solicitation site were associated with increased risk of HIV (AOR—2.4; 95% CI 1.2 to 4.7, p=0.001), while those frequenting lodges were at increased risk for CT/GC (AOR—6.3; 95% CI 1.9 to 20.6, p=0.03). Clients with HSV-2 infection were at substantially higher risk of being HIV-positive (AOR—10.4; 95% CI 6.1 to 17.7, p<0.0001). Conclusions: This study fills in important gaps in knowledge regarding clients of FSWs in Southern India. FSW clients clearly constitute an important bridging population between FSWs and their other sexual partners in the population. It is important to design and implement effective prevention and care programs for this well-hidden population.